On a function related to Ramanujan's Tau function - John A. Ewell (International Journal of Mathematics and Mathematical Sciences)
For the function ψ=ψ12, defined by ∑1∞ψ(n)xn=x∏1∞(1−x2n)12   (|x|<1), the author derives two simple formulas. The simpler of these two formulas is expressed solely in terms of the well-known sum-of-divisors function.